Instability Of Conical Shells With Multiple Dimples Under Axial Compression - Ifayefunmi, Olawale; Mahidan, Fairuz Mardhiah; Maslan, Mohamad Haidir (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2020)
Thin-walled conical shells are primary structures in offshore application. Presence of imperfection can considerably reduce the load carrying capacity of such structures when in use. This study examines the buckling behavior of axially compressed imperfect steel cones using the multiple perturbation load analysis (MPLA). This is both a numerical and experimental study. Eight conical shell test models were manufactured in pairs and collapsed under axial compression: two perfect, and the remaining six with MPLA imperfection amplitude, A, of 0.56, 1.12 and 1.68 having two equally-spaced dimples on each cones. Experimental test results for all the conical shell models and the accompanying numerical predictions are given in this paper. Repeatability of experimental data was good. The errors within each pair were 3%, 13%, 1% and 0%. In addition, there was a good comparison between experimental and numerical data. The ratio of experimental to numerical buckling loads varies from 0.91 to 1.13